Case Report: Neonatal Multi-System Inflammatory Syndrome Associated With SARS-CoV-2 Exposure in Two Cases From Saudi Arabia - Shaiba, Lana A.; Hadid, Adnan; Altirkawi, Khalid A.; Bakheet, Hind M.; Alherz, Aminah Mohammed; Hussain, Shaik Asfaq; Sobaih, Badr H.; Alnemri, Abdulrahman M.; Almaghrabi, Rana; Ahmed, Medina; Arafah, Maria A.; Jarallah, Abdullah; et al. (Frontiers in Pediatrics, 2021)
Background: Vertical transmission of SARS-COV-2 is under investigation. A few reports suggest the possibility of SARS-COV-2 transmission from the mothers to their neonates. Most neonates have mild symptoms but some develop multi system involvement and shock. Case Presentation: We report two cases of possible SARS-COV-2 vertical transmission from mothers to their neonates. The first case shows maternal infection with SARS-COV-2 in the second trimester followed by recurrent infection in the third trimester right before the delivery. The infant demonstrated respiratory distress soon after delivery along with myocardial dysfunction and multi-organ system involvement. The second case shows maternal infection with SARS-COV-2 at the time of delivery with preterm labor secondary to abruptio-placenta and resulted in a preterm neonate requiring none invasive ventilation with multi-system involvement in the context of persistently positive SARS-COV-2 PCR in the neonate. Both neonates were treated with IVIG along with steroids. Both neonates recovered fully and were discharged home. Conclusion: In neonates, COVID-19 usually presents as an asymptomatic or mild illness; some of them may develop a more severe course. Our two cases, however, demonstrate that multi-system involvement, although rare, but is possible. This report also supports the current evidence of possible vertical transmission from mothers to their neonates. This multi-system involvement might be under-reported and should be considered in neonates with respiratory distress when born to mothers suffering of COVID-19.